Vulgarisation de la methode du triple ensachage pour le stockage ameliore du niebe en zone sahelienne du Nord Cameroun: enjeux et perceptions paysannes - Folefack, D.; Sobda, A.; Tengomo, S.; Boukar, O.; Abdoulaye, Tahirou (2013)
The study reveals the stakes of the triple baggingmethod, assesses farmer perception about thistechnology and identifies the factors determiningtheir perception. One of the most limiting factors ofcowpea production is the storage. To solve thisproblem, Purdue University Improved CowpeaStorage Project introduced in 2010 in Cameroonthe PICS bag technology without chemical. Thesurvey revealed that pilot farmers were satisfied ofthe use of this technology. An assessment ofeconometric model pointed out an evidentcorrelation between socio-economic factors and thelevel of satisfaction of pilot farmers. Some variablesinfluenced significantly the probability of beingsatisfied, namely: the farmer experience in cowpeacropping, annual area covered by cowpea crops,the use of PICS bags without chemical, healthprotection and the potential use of PICS bags tostore other crops. Farmers are willing to adopt thistechnology for the storage of cowpea. A furthersurvey must be done in the future to assess thereal adoption rate and the impact of this technologyin this zone.